Enhanced photoelectrochemical performance of PbS sensitized Sb–SnO2/TiO2 nanotube arrays electrode under visible light illumination - Wu, Jia; Tang, Chengli; Xu, Hao; Yan, Wei (Journal of alloys and compounds, 2015)
•Sb–SnO2 is used to modify TiO2 NTAs by microwave method.•PbS is employed to sensitive Sb–SnO2/TiO2 NTAs by S-SILAR method.•Sb–SnO2 improves electrons transfer and PbS enhances visible light absorption.•The composite electrode shows enhanced photoelectrochemical properties.•The composite electrode exhibits high hydrogen evolution and high QE. The novel PbS sensitized Sb–SnO2/TiO2 nanotube arrays (NTAs) composite electrode (PbS/Sb–SnO2/TiO2 NTAs) was fabricated by microwave combined with sonication-assisted successive ionic layer adsorption and reaction technique (S-SILAR). The obtained electrodes were characterized by field-emission scanning electron microscopy (FE-SEM), energy-dispersive X-ray spectroscopy (EDS), X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS) and UV–Vis diffuse reflectance absorption spectra techniques. Enhanced photocurrent (15.52mA/cm2) of the PbS/Sb–SnO2/TiO2 NTAs electrode was observed and can be attributed to the facile photo-generated electrons transfer and enhanced charge separation efficiency. Furthermore, the PbS/Sb–SnO2/TiO2 NTAs composite electrode shows a higher H2 production rate than the Sb–SnO2/TiO2 NTAs electrode and PbS/TiO2 NTAs electrode. The results indicate that the PbS/Sb–SnO2/TiO2 NTAs electrode is a promising photoanode in visible photocatalytic water splitting.